(untitled) (Jagannath University Journal of Arts, 2026)
This paper explores the lived experience of educated, middle-class divorced women, focusing on the factors influencing their decision to divorce, the challenges they face post-divorce, and the coping strategies they adopt to address these challenges. Using a qualitative research approach, data were collected from eight divorced women residing in Dhaka city through in-depth interviews. The findings reveal that women experience subjugation, misery, and violence within marriage, which undermines their security and self-dignity. Drawing on Beck and Beck-Gernsheim‘s theory of personal relationships, marriages, and family patterns in late modernity, this research demonstrates that rather than being passive victims of these adversities, women actively choose to divorce to escape dysfunctional marriages. However, such agency is often not well received by the patriarchal society, resulting in a range of vulnerabilities and challenges in post-divorce life, including financial insecurity, social stigma, sexual harassment, emotional distress, and so on. In response, women seek education, formal employment, and entrepreneurship to overcome financial hardship, while adopting strategies to disregard negative social judgements as a coping mechanism. This paper emphasizes the need for a more gender-sensitive and women-friendly cultural shift to ensure women‘s security, freedom, and respect within marriage, which is crucial for maintaining healthy family dynamics and preventing divorce. Furthermore, in instances where divorce does occur, it is essential for families, communities, society, and the state to adopt supportive and positive attitudes toward divorced women, rather than stigmatizing them. Jagannath University Journal of Arts, v-5, i-01, 2025: p176-192